Systematic theology ; v. 1 - Hodge, Charles, 1797-1878 (Grand Rapids, MI Eerdmans, 1871)
Contents : v. 1 : Introduction; pt 1, Theology proper. Includes bibliographical references.
1952 reprint
Keywords: Theology, doctrinal